Pengembangan Sistem Monitoring dan Pelaporan Distribusi Barang Menggunakan Metodologi Waterfall dan Blackbox (Studi Kasus: PT. Mitra Mega Sinergi) - Jeli Sukaramah Zai; Handrie Noprisson (JSAI (Journal Scientific and Applied Informatics), 2025)
The digitalization era demands structured management of goods distribution data to improve performance and company competitiveness. This research aimed to develop a goods distribution data management system at PT. Mitra Mega Sinergi. By adopting the waterfall methodology, which consisted of a literature study followed by analysis and design of a web-based application, application implementation, blackbox testing to ensure functionality, and report writing as documentation of the system development results. The case study conducted at PT. Mitra Mega Sinergi identified issues in data distribution management, including data inaccuracies, tracking difficulties, and slow decision-making. Based on the research findings, the system consisted of a database to record user data, goods, and distribution processes. The goods class recorded the stock of goods, while the distribution class managed shipment transactions, including the user, the shipped goods, the destination, and the transaction time. The final report of this system consisted of reports such as the name of the goods, item code, type, unit, available stock, and stock in the warehouse, which were used to identify and monitor the availability of goods.